Effectiveness of Spinal Stabilization Exercises on Dynamic Balance in Adults with Chronic Low Back Pain - Yousef M. Alshehre; Khalid Alkhathami; Kelli Brizzolara; Mark Weber; Sharon Wang-Price (International Journal of Sports Physical Therapy)
# Background